Bile Pigments in Pulmonary and Vascular Disease - Ryter, Stefan W. (Frontiers in Pharmacology, 2012)
The bile pigments, biliverdin and bilirubin, are endogenously-derived substances generated during enzymatic heme degradation. These compounds have been shown to act as chemical antioxidants in vitro. Bilirubin formed in tissues circulates in the serum, prior to undergoing hepatic conjugation and biliary excretion. The excess production of bilirubin has been associated with neurotoxicity, in particular to the newborn. Nevertheless, clinical evidence suggests that mild states of hyperbilirubinemia may be beneficial in protecting against cardiovascular disease in adults. Pharmacological application of either bilirubin and/or its biological precursor biliverdin, can provide therapeutic benefit in several animal models of cardiovascular and pulmonary disease. Furthermore, biliverdin and bilirubin can confer protection against ischemia/reperfusion injury and graft rejection secondary to organ transplantation in animal models. Several possible mechanisms for these effects have been proposed, including direct antioxidant and scavenging effects, and modulation of signaling pathways regulating inflammation, apoptosis, cell proliferation, and immune responses. The practicality and therapeutic-effectiveness of bile pigment application to humans remains unclear.